HIV and syphilis infections and associated factors among patients in treatment at a Specialist Alcohol, Tobacco, and Drugs Center in São Paulo’s “Cracolândia” - Ribeiro,Ariadne (2020)
Abstract Introduction This study describes the epidemiological scenario of human immunodeficiency virus (HIV) and syphilis at the biggest specialist drug addiction center in Brazil. The great challenge is to find strategies to reduce the impact of inequality and discrimination and develop policies to protect individuals living with – or at risk of – infections. Methods During the period from January 1 to May 31, 2016, a cross-sectional study was conducted on which all patients (N = 806) seeking inpatient treatment were enrolled. A structured diagnostic interview and rapid tests were conducted initially, and diagnoses were confirmed by tests conducted at a venereal disease research laboratory (VDRL). Results HIV and syphilis rates were 5.86% and 21.9%, respectively. Women were nearly 2.5 times more likely to have syphilis. HIV infection was associated with unprotected sex (odds ratio [OR]: 3.27, p = 0.003, 95% confidence interval [95%CI]: 1.51-7.11), and suicidal ideation (OR: 6.63, p = 0.001, 95%CI: 3.37-14.0). Although only 1.86% reported injecting drugs at any point during their lifetimes, this variable was associated with both HIV and syphilis. Elevated rates of HIV and syphilis were observed in the context of this severe social vulnerability scenario. Conclusion The risk factors identified as associated with HIV and syphilis should be taken into consideration for implementation of specific prevention strategies including early diagnosis and treatment of sexually transmitted infections (STI) to tackle the rapid spread of STIs in this population.